1983
DOI: 10.1002/jctb.280330309
|View full text |Cite
|
Sign up to set email alerts
|

A study of biogas generation from coconut pith

Abstract: Biogas production from cowdung is well studied. Coconut pith is an agricultural waste available in large quantities in Kerala: the possibility of using coconut pith for biogas production was studied. It was found that coconut pith in combination with cowdung gives considerable amount of biogas, while alone it did not produce any gas. The optimum combination was found to be 60% pith and 40% cowdung.Study of dilution effect on the slurry showed that the optimum solid-liquid ratio is 1 : 20. Partial removal of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…It is essentially a ligno-cellulosic material that decomposes very slowly in soil, because its pentosan/lignin ratio is 1:0.30; the minimum required for moderately fast decomposition in the soil is 1:0.50 . It has been reported that coir pith in combination with cow dung gives a considerable amount of biogas . About 7.5 × 10 5 tons of coir pith is produced annually in India .…”
Section: Introductionmentioning
confidence: 99%
“…It is essentially a ligno-cellulosic material that decomposes very slowly in soil, because its pentosan/lignin ratio is 1:0.30; the minimum required for moderately fast decomposition in the soil is 1:0.50 . It has been reported that coir pith in combination with cow dung gives a considerable amount of biogas . About 7.5 × 10 5 tons of coir pith is produced annually in India .…”
Section: Introductionmentioning
confidence: 99%
“…The energy from biomass holds a promising scope under Indian conditions because this sector encourages the efficient management of agricultural waste in an eco-friendly way (Stalin et al, 2012). Biogas production was observed from codigestion of cow dung with rice husk, coconut pith and rice chaff (Elijah et al, 2009;Radhika et al, 1983;Vivekanandan and Kamaraj, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Methanobrevibacter (Conrad et al 1989, Rajagopal et al 1988, Asakawa et al 1993, Min Ζ. et al 1997, Joulian et al 1998, Adachi 1999). Μεθέηεξ έπμοκ αζπμθδεεί ιε ηδκ παναβςβή ιεεακίμο απυ οπμθείιιαηα θνμφηςκ υπςξ: ηανφδαξ (Radhika et al 1983), ιήθμο (Hills ηαζ Roberts 1982) ιπακάκαξ (Sharma S. et al 1988) ηαζ πμθθχκ άθθςκ. Δπζπθέμκ, έπμοκ δζαηεεεί βζα πχκεοζδ οπμθείιιαηα αβνμηζηήξ επελενβαζίαξ.…”
Section: μδθτλοσροφηκζ κεζαλνγέλεζεunclassified